A pilot study of the acceptability, feasibility and safety of yoga for chronic pain in sickle cell disease. (June 2021) - Bakshi, Nitya; Cooley, Anthony; Ross, Diana; Hawkins, Lauren; Sullivan, Marlysa; Astles, Rachel; Sinha, Cynthia; Katoch, Deeksha; Peddineni, Manasa; Gee, Beatrice E.; Lane, Peter A.; Krishnamurti, Lakshmanan
Highlights: Patients with SCD and chronic pain have a positive opinion of yoga. There are barriers to feasibilty of an in-person group yoga intervention for chronic pain in SCD. Abstract: Objectives: To determine the acceptability, feasibility and safety of yoga for chronic pain in sickle cell disease. Design and Setting: In Part A of this two-part study, adolescents with SCD and chronic pain (Group 1) and their parent (Group 2) completed a survey designed to capture pain characteristics, attitudes and practices related to yoga, and potential acceptability of a yoga program. In Part B, the study assessed the feasibility and safety of an instructor-led group yoga program. The study was registered on clinicaltrials.gov (NCT03694548). Intervention: Eight instructor-led group yoga sessions. Main Outcome Measures: Feasibility and safety outcomes were chosen a priori, as follows: 1) Proportion of adolescent patients with SCD and chronic pain approached that consent to participate in Part A, 2) Proportion of adolescent participants enrolled in Part A that consent to participate in Part B, 3) Proportion of participants enrolled in Part B that attend at least 6 of 8 yoga sessions, 4) Proportion of participants enrolled in Part B with an ED visit or a hospitalization for pain within 24 h of completion of each yoga session, 5) Proportion of participants in Part B who complete all study assessments before, and at the end of the yoga program, 6) Adherence to submission of pain diary. Results: The median age of 15 patient participants in Part A was 16 (IQR 14−17), and 14 parents was 43.5 (IQR 42−51). Most participants were female. Most participant responses indicated a positive opinion of yoga. Nine adolescents (60 %) from Part A participated in Part B of the study. The median age of 9 participants in Part B was 17 (IQR 15−18), and 5 of the 9 participants were female (53.3 %). Only one participant was able to attend 3 of the 8 yoga sessions offered, and did not experience any ED visits or hospitalizations following the yoga sessions. None of the other feasibility endpoints were met in this study. Conclusions: Patients with SCD and chronic pain overall have a positive opinion of yoga, but there are challenges with recruitment and retention of participants in a clinical trial of yoga, and barriers to feasibility of an in-person group yoga intervention.